Konflik Batin Tokoh Nonoguchi Osamu dalam Novel Akui Karya Keigo Higashino: Tinjauan Psikologi Sastra - Afisah, Yusra; El Risman, Yunita (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2025)
This research examines the internal conflicts experienced by Nonoguchi Osamu in Keigo Higashino's novel Akui through the lens of Sigmund Freud's psychoanalytic theory, which comprises three key aspects: the id, ego, and superego. The study adopts a qualitative descriptive method, with data collection techniques including close reading and note-taking. The findings reveal that Nonoguchi Osamu's internal conflicts are predominantly ego-driven. His ego motivates him to undertake extreme actions for personal benefit, including killing his friend, fabricating evidence, and tarnishing his friend's reputation as a successful young writer. Furthermore, Nonoguchi's internal turmoil is exacerbated by his fear of his dark past being uncovered. However, his superego also exerts influence, reflecting his retention of moral values. This is evident in his hesitations to commit murder and his lingering concern for his friend. Ultimately, Nonoguchi accepts the consequences of his actions, illustrating the intricate interplay of the id, ego, and superego in shaping his psychological conflicts.